2010
DOI: 10.1007/s11270-010-0551-5
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of Stabilized Fowl Manure as Soil Amendment and Its Implication on Organic Agriculture Nutrition Management

Abstract: A major input in intensive organic agriculture is nutrient-rich liquid fertilizers. Guano and other fowl manure are frequently digested in water extracts, and the supernatant is supplied as fertilizer. The resultant manure biowaste (MBW) is commonly disposed of to the environment, posing potential pollution and health risks. The study aims were to determine two types of fowl MBWs for their chemical properties before and after lime treatment and to test their reuse potential as soil amendment. Guano and layer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Subsamples were characterized for BOD 5 and OM content as described above. Estimation of BOD 5 using dry samples allowed normalizing and comparing the data of the two systems (Posmanik et al 2011). The differences between initial and final values for BOD 5 and OM were used for the calculation of digestion efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…Subsamples were characterized for BOD 5 and OM content as described above. Estimation of BOD 5 using dry samples allowed normalizing and comparing the data of the two systems (Posmanik et al 2011). The differences between initial and final values for BOD 5 and OM were used for the calculation of digestion efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…The FC count was below detection limits, and lower than the upper limit of 10 3 CFU g −1 for (not detected) <10 2 <10 3b a High quality standards = suitable for biowaste reuse in organic farming (Amlinger et al 2004) b Meets the EU standards for "category 3 low-risk biowaste" (European Parliament and Council 2002) c "Class A" standards for biosolids, allowing unrestricted land application (USEPA 1994) unrestricted agricultural land spreading (Table 3). Yet, it should be noted that an earlier report by Posmanik et al (2011) suggested that digested guano should be land spread with care as it might have some negative effect on plants such as parsley.…”
Section: Quality Of Digested Manure Residue In the Eumentioning
confidence: 99%